Small bowel protection against NSAID-injury in rats: Effect of rifaximin, a poorly absorbed, GI targeted, antibiotic. (February 2016) - Fornai, Matteo; Antonioli, Luca; Pellegrini, Carolina; Colucci, Rocchina; Sacco, Deborah; Tirotta, Erika; Natale, Gianfranco; Bartalucci, Alessia; Flaibani, Marina; Renzulli, Cecilia; Ghelardi, Emilia; Blandizzi, Corrado; et al.
Graphical abstract: Abstract: Nonsteroidal anti-inflammatory drugs, besides exerting detrimental effects on the upper digestive tract, can also damage the small and large intestine. Although the underlying mechanisms remain unclear, there is evidence that enteric bacteria play a pivotal role. The present study examined the enteroprotective effects of a delayed-release formulation of rifaximin-EIR (R-EIR, 50 mg/kg BID, i.g.), a poorly absorbed antibiotic with a broad spectrum of antibacterial activity, in a rat model of enteropathy induced by indomethacin (IND, 1.5 mg/kg BID for 14 days) administration. R-EIR was administered starting 7 days before or in concomitance with IND administration. At the end of treatments, blood samples were collected to evaluate hemoglobin (Hb) concentration (as an index of digestive bleeding). Small intestine was processed for: (1) histological assessment of intestinal damage (percentage length of lesions over the total length examined); (2) assay of tissue myeloperoxidase (MPO) and TNF levels, as markers of inflammation; (3) assay of tissue malondialdehyde (MDA) and protein carbonyl concentrations, as an index of lipid and protein peroxidation, respectively; (4) evaluation of the major bacterial phyla. IND significantly decreased Hb levels, this effect being significantly blunted by R-EIR. IND also induced the occurrence of lesions in the jejunum and ileum. In both intestinal regions, R-EIR significantly reduced the percentage of lesions, as compared with rats receiving IND alone. Either the markers of inflammation and tissue peroxidation were significantly increased in jejunum and ileum from IND-treated rats. However, in rats treated with R-EIR, these parameters were not significantly different from those observed in controls. R-EIR was also able to counterbalance the increase in Proteobacteria and Firmicutes abundance induced by INDO. To summarize, R-EIR treatment significantly prevents IND-induced intestinal damage, this enteroprotective effect being associated with a decrease in tissue inflammation, oxidative stress and digestive bleeding as well as reversal of NSAID-induced alterations in bacterial population.